THE IMPACT OF CAUDAL BLOCK ANESTHESIA ON POSTOPERATIVE COMPLICATIONS IN DISTAL HYPOSPADIAS SURGERY: A MULTI-CENTER RANDOMIZED CONTROLLED TRIAL - Toni Risteski; Mustafa Azizoğlu; Sergey Klyuev (My University, 2024)
Aim of the study: This study aimed to assess the effect of caudal block anaesthesia on the outcomes of distal hypospadias surgery. Methods: The patients were randomly divided into two groups. Group 1 (n=) received caudal block anesthesia Group 2 (n=) received no caudal block. The postoperative complications were compared. All patients underwent repair with the TIPU technique. Results: Group 1, consisting of 101 patients, and Group 2, with 78 patients, were evaluated for the prevalence of complications. The findings revealed that meatal stenosis occurred in 6.9% of Group 1 and 7.7% of Group 2, urethrocutaneous fistula in 6.9% of Group 1 compared to 5.1% in Group 2, glans dehiscence in 2% of Group 1 and 3.8% of Group 2, and urethral stenosis was observed in 2% of patients in both groups. Notably, there were no instances of urethral diverticula in either group. Statistical analysis showed no significant differences in the rates of meatal stenosis (p=0.846), urethrocutaneous fistula (p=0.619), glans dehiscence (p=0.453), and urethral stenosis (p=0.793) between the two groups. Conclusion: The study demonstrated that caudal block anesthesia does not significantly increase the postoperative complications in distal hypospadias surgery, with similar complication rates observed in both study groups.
European Paediatric Surgeons’ Association, Annual Congress 2024